2003
DOI: 10.1002/chem.200304913
|View full text |Cite
|
Sign up to set email alerts
|

How Nucleophilic Are Diazo Compounds?

Abstract: The kinetics of the reactions of benzhydryl cations with eight diazo compounds 1 a-g were investigated photometrically in dichloromethane. The nucleophilicity parameters N and slope parameters s of these diazo compounds were derived from the equation log k (20 degrees C)=s (E+N) and compared with the nucleophilicities of other pi systems (alkenes, arenes, silyl enol ethers, silyl ketene acetals). It is shown that the nucleophilic reactivities of diazo compounds cover more than ten orders of magnitude, being co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
102
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 60 publications
(47 reference statements)
3
102
0
2
Order By: Relevance
“…The bis( p-dimethylamino)benzhydryl cation reacts with diazomethane 1.3 × 10 4 times faster than with diphenyldiazomethane 7. The nucleophilicity parameter N of 7 has been determined [38], but the electrophilicity E of thiobenzophenone is unknown.…”
Section: Measurement and Discussion Of Rate Constantsmentioning
confidence: 99%
“…The bis( p-dimethylamino)benzhydryl cation reacts with diazomethane 1.3 × 10 4 times faster than with diphenyldiazomethane 7. The nucleophilicity parameter N of 7 has been determined [38], but the electrophilicity E of thiobenzophenone is unknown.…”
Section: Measurement and Discussion Of Rate Constantsmentioning
confidence: 99%
“…Chemie alkanes, [62] ketene acetals, [52,63] enol ethers, [52,64] water, [65] transition metal p-complexes, [52,66] alkenes, [52] hydride donors, [49,67] and arenes [52,68] with benzhydrylium ions follow linear correlations with the electrophilicity parameter E. In some cases it has been shown that these correlation lines bend for k > 10 8 m À1 s À1 and asymptotically approach the diffusion Figure 8. Rate constants for the reactions of carbenium ions with allylsilanes.…”
Section: Methodsmentioning
confidence: 96%
“…[8,9] The most extensive nucleophilicity scale, [10,11] presently available, has been derived from the rate constants of the reactions of benzhydrylium ions with alkenes, arenes, enol ethers, ketene acetals, [12] enamines, [13] allyl element compounds, [14] transition-metal p-complexes, [15] diazoalkanes, [16] and delocalized carbanions [17][18][19] (p-nucleophiles), amines, [20] alcohols, [21] alkoxides, [22] phosphanes, [23] inorganic anions [24][25][26][27] (n-nucleophiles), and a variety of hydrides [28][29][30][31] (s-nucleophiles); these rate constants were subjected to a least-squares minimization on the basis of Equation (3) [10,11] in which k is the second-order rate constant at 20 8C and E is a nucleophileindependent electrophilicity parameter.…”
mentioning
confidence: 99%